Catalytic effect of trifluoroacetamido group on thermally induced ring-opening polymerization of 1, 3-benzoxazine and formation of arylamine Mannich bridge structure. (April 2016) - Situ, Yue; Zhu, Zuwei; Huang, Hong
The autocatalytic ring-opening polymerization behavior of trifluoroacetamido group containing benzoxazine (FBA) is reported and its curing process was monitored by in situ proton nuclear magnetic resonance and Fourier transform infrared spectra analysis. The ring-opening polymerization temperature of FBA is significantly lower than that of typical 1, 3-benzoxazine (BA), which can be attributed to higher stability of benzoxazine zwitterionic ion intermediate due to strong electron-withdrawing effect of trifluoroacetamido substituent. Arylamine Mannich bridge structure is found to form during polymerization, thereby enhancing the thermal stability of FBA homopolymer (poly-FBA). Differential scanning calorimetric analysis indicates that FBA effectively catalyzes the copolymerization of FBA and BA monomers at a temperature even lower than the polymerization temperature of pure FBA monomer, and the resultant copolymer exhibits higher glass transition temperature than either FBA or BA homopolymer, indicating promising possibility of FBA as reactive comonomer of polybenzoxazine systems for curing acceleration and performance improvement.